KONSTRUKSI KHUDI DALAM PERPOLITIKAN INDONESIA KONTEMPORER - Utomo, Wahyu Wiji; Zulkarnain, Zulkarnain (Jurnal Ushuluddin, 2019)
Indonesia's political chaos starting from Corruption, Collusion and Nepotism is an unresolved problem and there has been no bright spot to date. There is no formula and the right solution to solve this problem. It is likened to a building, Indonesia is a strong country but very easily collapsed due to political problems, ranging from individuals and groups.Therefore it is necessary to have a strong and sturdy construction to support the building so that it does not easily collapse. Reconstruction built by M.Iqbal with khudi gave birth to a healthy and dynamic politics. As for things that can strengthen the mind: Love, Faqr, courage or enthusiasm, Tolerance, Halal business, and honest and creative work. This can be used as a reconstruction in contemporary Indonesian politics. Love and responsibility will color individuals who are involved in politics. Khudi as a philosophical thought serves to strengthen Indonesia's easily shaken political foundation.The type of research used in this research is descriptive analysis which in this case political reconstruction will be based on M.Iqbal theory, namely gambling. library research method. As a recommendation to overcome the solution of various problems in contemporary Indonesian politics, the political reconstruction offered by M.Iqbal with his opinion was deemed necessary and able to answer the political problem.